Pediatric rosacea in a patient with a dark phototype: Clinical and dermoscopic features. Issue 12 (13th October 2020) - Chabchoub, Ines; Litaiem, Noureddine; Zeglaoui, Faten
Abstract: Rosacea is rare in children and patients with dark phototype. Dermoscopy helps make the correct diagnosis. Positive family history of rosacea is reported in affected children, which suggests a strong familial inheritance of the disorder. Abstract : Rosacea is rare in children and patients with dark phototype. Dermoscopy helps make the correct diagnosis. Positive family history of rosacea is reported in affected children, which suggests a strong familial inheritance of the disorder.